Impoliteness Strategy Used by the Main Character in “Enola Holmes 2 (2022)” - Sabatini, Mayola; Ambarwati, Rosita; Vendityaningtyas, Vita (Universitas PGRI Madiun, 2023)
The purpose of this study is to analyze and present the types of impoliteness strategy and the function uttered by the main character in Enola Holmes 2 movie. The method being used was qualitative method. The researcher used the data from the movie Enola Holmes 2. Apart from writing the movie script, data is collected through a series of observational steps, including watching the film, downloading the script, identifying and labeling the impoliteness strategy used in the movie, and categorizing each piece of data according to Culpeper (2005). As a result, five types of rudeness strategies are identified that they are bald on record impoliteness (28%), positive impoliteness (14%), negative impoliteness (38%), off-record impoliteness (17%), withhold politeness (3%). The function of each strategy are using direct statement, disassociating from others, ignoring the others, using inappropriate identity markers, condescending or threatening others and talking back, employing insincere politeness and being silent. The mother of the main character has an education, and she lives in a society that does not value women's rights, which influences her decision to use the impoliteness strategy.